2017
DOI: 10.1007/s13592-017-0535-1
|View full text |Cite
|
Sign up to set email alerts
|

Nosema ceranae disease of the honey bee (Apis mellifera)

Abstract: The presence of honey bees in our landscapes has long invoked images of vitality, diligence, and cooperation. Unfortunately, the current state of bee health paints a rather different picture. The survival of honey bees, as well as the livelihoods of those who benefit from their labor, is under threat from several detractors to bee health. Exposure to pesticides, poor forage, mite parasites, and pathogens has resulted in high annual death of colonies in the USA, Europe, and other parts of the world. Among the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 182 publications
(239 reference statements)
4
86
0
2
Order By: Relevance
“…While N. ceranae was ubiquitous in the study population, the inherently native species N. apis was only present in 1% of the bees, and exclusively in mixed infections with N. ceranae. This is in line with the previous finding that N. ceranae is replacing N. apis (Goblirsch, 2018;Paxton, Julia, Seppo, & Ingemar, 2007); however, its large prevalence and high concentrations in healthy, well-performing colonies argue against the suspicion that N. ceranae, by itself, could be more virulent than N. apis (Higes, Garcia-Palencia, Martin-Hernandez, & Aranzazu, 2007;Paxton et al, 2007). It should be pointed out that since all of our measurements were done on RNA level, the reported concentrations of the organisms with a DNA genome (i.e., all bacteria and parasites) are not directly comparable to those reported in other studies from measurements on DNA level and give an indication of metabolic activity rather than cell numbers.…”
Section: Discussionsupporting
confidence: 93%
“…While N. ceranae was ubiquitous in the study population, the inherently native species N. apis was only present in 1% of the bees, and exclusively in mixed infections with N. ceranae. This is in line with the previous finding that N. ceranae is replacing N. apis (Goblirsch, 2018;Paxton, Julia, Seppo, & Ingemar, 2007); however, its large prevalence and high concentrations in healthy, well-performing colonies argue against the suspicion that N. ceranae, by itself, could be more virulent than N. apis (Higes, Garcia-Palencia, Martin-Hernandez, & Aranzazu, 2007;Paxton et al, 2007). It should be pointed out that since all of our measurements were done on RNA level, the reported concentrations of the organisms with a DNA genome (i.e., all bacteria and parasites) are not directly comparable to those reported in other studies from measurements on DNA level and give an indication of metabolic activity rather than cell numbers.…”
Section: Discussionsupporting
confidence: 93%
“…resulted in interactive effects on performance of survival of individual bees (Alaux et al 2010, Pettis et al 2013) (but see Goblirsch [2018] for an overview), we found no interactive effects of exposure to imidacloprid and Nosema spp. resulted in interactive effects on performance of survival of individual bees (Alaux et al 2010, Pettis et al 2013) (but see Goblirsch [2018] for an overview), we found no interactive effects of exposure to imidacloprid and Nosema spp.…”
Section: Interactive Effectsmentioning
confidence: 63%
“…Although previously exposures to neonicotinoids and Nosema spp. resulted in interactive effects on performance of survival of individual bees (Alaux et al 2010, Pettis et al 2013) (but see Goblirsch [2018] for an overview), we found no interactive effects of exposure to imidacloprid and Nosema spp. at the exposure and measurement levels in this field-realistic study.…”
Section: Interactive Effectsmentioning
confidence: 63%
See 1 more Smart Citation
“…with adverse consequences for their hosts [23,24]. Ingested N. ceranae spores germinate in the bee midgut, penetrate host cells and produce additional spores within 48-96 h that either infect adjacent cells or are passed in the faeces [25]. Viable spores may then be consumed during cleaning or grooming, and some are left behind on the flower after an infected bee visits [21,22].…”
Section: Introductionmentioning
confidence: 99%